A Placebo-Controlled Trial of Riboflavin for Enhancement of Ultramarathon Recovery - Martin D. Hoffman; Taylor R. Valentino; Kristin J. Stuempfle; Brandon V. Hassid (SpringerOpen, 2017)
Abstract Background Riboflavin is known to protect tissue from oxidative damage but, to our knowledge, has not been explored as a means to control exercise-related muscle soreness. This study investigated whether acute ingestion of riboflavin reduces muscle pain and soreness during and after completion of a 161-km ultramarathon and improves functional recovery after the event. Methods In this double-blind, placebo-controlled trial, participants of the 2016 161-km Western States Endurance Run were assigned to receive a riboflavin or placebo capsule shortly before the race start and when reaching 90 km. Capsules contained either 100 mg of riboflavin or 95 mg of maltodextrin and 5 mg of 10% ß-carotene. Subjects provided muscle pain and soreness ratings before, during, and immediately after the race and for the 10 subsequent days. Subjects also completed 400-m runs at maximum speed on days 3, 5, and 10 after the race. Results For the 32 (18 in the riboflavin group, 14 in the placebo group) race finishers completing the study, muscle pain and soreness ratings during and immediately after the race were found to be significantly lower (p = .043) for the riboflavin group. Analysis of the 400-m run times also showed significantly faster (p < .05) times for the riboflavin group than the placebo group at post-race days 3 and 5. Both groups showed that muscle pain and soreness had returned to pre-race levels by 5 days after the race and that 400-m run times had returned to pre-race performance levels by 10 days after the race. Conclusions This preliminary work suggests that riboflavin supplementation before and during prolonged running might reduce muscle pain and soreness during and at the completion of the exercise and may enhance early functional recovery after the exercise.